2015
DOI: 10.4028/www.scientific.net/jera.18.123
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Verification of Force Feedback for Rehabilitation Robot

Abstract: Unlike conventional robots, the equipment provided with pneumatic artificial muscles cannot integrate standard systems for force measurement. Applied measurement system involves specific attributes and requirements for pneumatic muscles. Force feedback of rehabilitation device equipped with pneumatic muscles was experimentally verified under the laboratory condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…As has been stated above, Data Matrix codes can be used to label logistic units, parts, warehousing positions, but also to navigate automated robots in production engineering [3,6,17,20].…”
Section: Resultsmentioning
confidence: 99%
“…As has been stated above, Data Matrix codes can be used to label logistic units, parts, warehousing positions, but also to navigate automated robots in production engineering [3,6,17,20].…”
Section: Resultsmentioning
confidence: 99%
“…The third area is advertising and marketing actions. In production engineering, Data Matrix codes can be used to designate logistic units, parts, warehousing positions, but also to navigate automated robots [22,23,24,25]. Due to their low cost, accuracy, speed, reliability, flexibility and efficiency, as well as the ability to record large amounts of data on a small area, they still have a great advantage in industrial applications.…”
Section: Resultsmentioning
confidence: 99%
“…Min et al [ 33 ] showed that in the rehabilitation training process, a combination of sensory stimulation, including visual and tactile stimulation, can provide timely and correct behavioural guidance and feedback for patients, which is conducive to reshaping the motor perception loop. The force-feedback hand rehabilitation robot used in this study provides force tactile stimulation and timely and effective sensorimotor information feedback to help patients better adjust their finger movements and complete grasping [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%